PENGEMBANGAN PERANGKAT PRATIKUM KARAKTERISTIK KAPASITOR MODEL INKUIRI TERBIMBING BERBANTUAN WIRELESS DATA LOGGING - Sri Rezeki; Muchlas Muchlas; Ishafit Ishafit (Universitas Muhammadiyah Semarang, 2018)
This study aims to develop a practicum tool in the form of student worksheets and wireless data logging systems for learning guided inquiry models of capacitor characteristic material. The model used is the ADDIE development model which includes 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The tools developed have been validated by experts using instruments in the form of giving questionnaires with predetermined criteria and indicators. From the results of the validation, it was obtained the assessment of the objective aspects, the truth aspects of the concept, aspects of clarity of sentence, aspects of physical appearance and practical aspects of getting an average score of 85.18%, included in the Very Eligible category. Based on the results of the trial the student response tool after practicum got an average score of 89.67% included in the very feasible category. Based on the assessment that has been done, it can be concluded that,the principle of capacitor characteristics of the model of guided inquiry assisted wireless data logging is feasible to use and can be applied. The advantages of the model of guided inquiry inquiry assisted by wireless data logging are acquisition of data assisted by wireless data logging faster, simplifying data retrieval, data obtained can be analyzed directly using Smarthpone, effective and efficient in overcoming the constraints of limited experimental equipment.The drawback is that the student worksheets need time intervals for each step of inquiry learning Keywords: Development of devices, characteristics of capacitors, guided inquiry models, wireless data logging